The Social Construction and Context of Domestic Violence in Wakiso District, Uganda - Kaye, Dan K.; Mirembe, Florence; Ekstrom, Anna Mia; Bantebya, Grace; Johansson, Annika (An International Journal for Research, Intervention and Care, 2005)
This study explored community perceptions of factors associated with domestic violence, with an emphasis on events occurring during pregnancy. Ten focus group discussions, 14 key-informant interviews and four case vignettes were conducted in Wakiso district, Uganda between August and December 2003. Data were analyzed using thematic content analysis. Perceived motives and meanings, triggering as well as associated factors, perceived coping mechanisms and community support available for reducing domestic violence, especially that occurring during pregnancy, were identified. Urban migration, changing cultural values and men’s unemployment shift the balance of power in gender relations. Resultant male uncertainty and gender antagonism is associated with domestic violence. Family institutions such as extended family structure, relatives and in-laws were perceived as offering little protection. Factors triggering violence included failed negotiation of sexual relations, disagreement concerning the division of labor within the household and misconceptions about the physical and physiological changes, both dietary and behavioral, which occur in pregnancy.
Keywords: Domestic violence; Social context; Risk factors; Pregnancy; Uganda